2022
DOI: 10.5433/1679-0359.2022v43n4p1403
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of soil loss by water erosion in the Tietê River Hydrographic Basin, São Paulo, Brazil

Abstract: Since the mid-16th century, the Tietê River has been an important route for the territorial occupation and exploitation of natural resources in the interior of São Paulo and Brazil. Currently, the Tietê River is well known for environmental problems related to water pollution and contamination. However, little attention has been focused on water erosion, which is a serious issue that affects the soils and waters of the hydrographic basin. Thus, this work aimed to estimate soil loss caused by water erosion in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In areas containing annual crops, high concentrations of nutrients and predominantly silt and clay were verified in the soil runoff, which has a strong relation with particle size due to cation exchange capacity [59]. This sediment runoff to the rivers may contaminate the water resources and the aquatic biota [66][67][68][69], which could be consumed by people [70,71], or the water contaminated with pesticides may be used for crop irrigation [72] or distributed to residences for human consumption, as observed by Panis et al [73] studying 127 grainproducing municipalities in Parana State, Brazil, which revealed contamination of drinking water and that contamination may increase the risk of cancer. In the Brazilian Amazon, pesticides were detected in aquatic ecosystems and sediments near a large zone of soybean production in the Santarém region [74], in the surface and ground waters, in drainage sediments in the indigenous lands surrounded by oil palm monoculture [75], and in aquatic and terrestrial ecosystems in the Brazilian Pampa [76].…”
Section: Factors Influencing Soil Degradation and The Need To Take Ca...mentioning
confidence: 99%
“…In areas containing annual crops, high concentrations of nutrients and predominantly silt and clay were verified in the soil runoff, which has a strong relation with particle size due to cation exchange capacity [59]. This sediment runoff to the rivers may contaminate the water resources and the aquatic biota [66][67][68][69], which could be consumed by people [70,71], or the water contaminated with pesticides may be used for crop irrigation [72] or distributed to residences for human consumption, as observed by Panis et al [73] studying 127 grainproducing municipalities in Parana State, Brazil, which revealed contamination of drinking water and that contamination may increase the risk of cancer. In the Brazilian Amazon, pesticides were detected in aquatic ecosystems and sediments near a large zone of soybean production in the Santarém region [74], in the surface and ground waters, in drainage sediments in the indigenous lands surrounded by oil palm monoculture [75], and in aquatic and terrestrial ecosystems in the Brazilian Pampa [76].…”
Section: Factors Influencing Soil Degradation and The Need To Take Ca...mentioning
confidence: 99%
“…Soil is a three-phase system that consists of solid particles, liquid, and gas, but also species that create a dynamic and complex ecosystem and is among the most precious resources to humans. On the other hand, soil erosion by water is acknowledged as a primary concern in the degradation of soil quality and functionality (Billi, & Spalevic, 2022;Saggau et al, 2022;Stefanidis et al, 2022;Lense et al, 2022;Chalise et al, 2019;Spalevic et al, 2017;Borrelli et al, 2016;Lal, 2014). The ever-growing availability of earth observation (EO) data and the well-established use of geographic information systems (GIS) during the last decades leads to the development of automated geospatial workflows for the estimation and mapping soil losses (Dominici et al, 2021;.…”
Section: Introductionmentioning
confidence: 99%
“…The soil is the base of a sustainable agricultural system; it is the key for food and energy production, a reservoir of water and nutrients [1][2][3], and a filter for water and contaminants [4]. However, inadequate soil management may significantly negatively impact the environment [5][6][7], crop development and yield [8][9][10][11][12], natural resources such as air and water [13][14][15], and human and animal health [16,17]. Soil management practices that favor soil and water conservation and the improvement of soil functions and structure are preferable.…”
mentioning
confidence: 99%